CLINICAL APPROACH IN MIRIZZI SYNDROME: A RETROSPECTIVE COMPARATIVE STUDY - Correia, Paulo Costa (2023)
Introduction: The Mirizzi syndrome consists of the obstruction either of the common hepatic duct or the choledocus, secondary to the impact of calculus in the cystic duct or in the gallbladder infundibulum. According to the Csendes classification, Mirizzi syndrome is divided into five types that involve different surgical procedures. Materials and methods: After a literature review, fifteen patients with Mirizzi Syndrome are retrospectively described between 2008 and 2018 at the Unidade Saude da Guarda (ULSG). The clinical records were reviewed. Clinical data, gender, clinical condition, test results, operative procedures and type of Mirizzi syndrome (according to Csendes) were examined. Results: Of the 15 patients, 11 (73,3%) were women and 4 (26,7%) men. All of them (100%) showed abdominal pain, 14 (93,3%) nausea and vomit, 10 (66,7%) symptoms of cholangitis / acute cholecystitis, 5 (33%) recurrent jaundice, 4 (26,6%) choluria and weight loss and 2 (13,3%) itch. Every cases of Mirizzi syndrome was diagnosed intraoperatively and requiring conversion to laparotomy. Were identified 5(33,3%) cases with type III, 4 (26,6%) with type I, 3 (20%) with type II, 2 (13,3%) with type IV and 1 (6,7%) with type V. In 5 (33,3%) patients was treated with cholecystectomy and bilio-digestive anastomosis on Roux-en-Y, 3 (20%) by total cholecystectomy with Kher drain, 2 (13,3%) by total cholecystectomy, partial and partial with Kher drain, and finally 1 (6,6%) by cholecystectomy with Kher drain with suture of the gastric orifice. Conclusion: The treatment of Mirizzi Syndrome is a diagnosis and surgical challenge. Despite the era of laparoscopic cholecystectomy, the laparotomic treatment of Mirizzi syndrome should be the standard procedure.